Intestinal Parasitic Infections among School Going Children in Kathmandu Valley, Nepal - Oli, Renisha; Katuwal, Nikesh; Khadka, Nirjala; Shrestha, Manish; Neupane, Mukesh; Angbuhang, Khadga Bikram; Dumre, Shyam Prakash; Adhikari, Nabaraj (Tribhuvan University Journal of Microbiology, 2022)
Objectives: In order to assess the Intestinal Parasitic infections from the School Going Children of Kathmandu Valley, this study analyzed the proportion of parasitic infection from the stool samples. Methods: Stool samples were collected from two schools of Kathmandu and analyzed for the assessment of intestinal parasites from May to June, 2018. The assessment of intestinal parasites was performed by Direct Microscopy and Formol ether Sedimentation technique and Modified Ziehl-Neelsen Staining was performed for the confirmation of Coccidian parasites. Results: The result is that out of 165 stool samples, intestinal parasites were detected in 28 (16.9%) samples and among them, 13 (46.4%) were protozoa and 15 (53.6%) were helminthes. A total of nine different parasites were recorded in the study. Among them, Taenia spp 5 (17.85%) for helminthes and G. lamblia 5 (17.85%) for protozoans was dominant and the least dominant organism for helminthes was H. diminuta (3.58%), for protozoans C. parvum (3.58%). Among the participants, more females were infected with intestinal parasite than male with majority from age group 13-15 years (23.1%). The distribution of parasites was higher among the students who drank water without treatment. Out of 28 intestinal parasites, 14/69 (20.3%) students showed the positive cases i.e. who drank water without treating followed by 13/70 (17.1%) students who filtered before drinking. The students who drank water after boiling 1/26 (3.8%) showed less distribution of parasites. The distribution of parasites was higher in the students who washed hands only with water on the basis of hand washing habits before eating i.e. 15/80 (18.7%). The distribution of parasites was higher among the students who bite their nail sometimes i.e. 15/76 (19.7%) as compared to the student who never bite their nail 13/89 (14.6%). Conclusion: Intestinal parasite is still a major health problem among the school going children in Nepal. Therefore, the infection preventive measures and school health awareness activities should continue.